2005
DOI: 10.1631/jzus.2005.b0125
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of epigallocatechin-3-gallate to LNCaP cells in the presence of Cu2+

Abstract: Epigallocatechin-3-gallate (EGCG) has shown remarkably anti-cancer activity, with its bioactivity being related to reactive conditions, such as pH and metal ions. The present study investigated the degradation of EGCG and its effect on prostate cancer cell in the presence of Cu 2+. EGCG was incubated with prostate cancer cells, LNCaP, pretreated with or without Cu 2+ . EGCG in F-12 medium was quantified using HPLC and the viability of cells was assessed by gel electrophoresis, flow cytometry, and electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The structure of oviduct wall of M. nipponense is similar to that found in other shrimp (Macrobrachium carcinus, Macrobrachium rosebergii) (Deng, 2000;Yu and Lu, 2005), but is different from that of crabs (Decapoda, Braclyrora) and Isopoda (Hartnoll, 1968;Hryniewiecka-Szyfter and Tyczewska, 1992;Jensen et al, 1996).…”
Section: Oviduct Wallsupporting
confidence: 77%
See 2 more Smart Citations
“…The structure of oviduct wall of M. nipponense is similar to that found in other shrimp (Macrobrachium carcinus, Macrobrachium rosebergii) (Deng, 2000;Yu and Lu, 2005), but is different from that of crabs (Decapoda, Braclyrora) and Isopoda (Hartnoll, 1968;Hryniewiecka-Szyfter and Tyczewska, 1992;Jensen et al, 1996).…”
Section: Oviduct Wallsupporting
confidence: 77%
“…The oviduct of shrimp, M. carcinus or M. rosebergii, is also composed of a thin layer of connective tissue and a layer of columnar epithelial cells (Deng, 2000;Yu and Lu, 2005). While the oviduct of the Dungeness crab, Cancer magister, is composed of a layer of columnar epithelium cell with a thin chitin lining, and the gonoduct wall is composed of three layers: the columnar epithelium, chitin, and connective tissue (Jensen et al, 1996).…”
Section: Oviduct Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several reports have focused on the interactions of catechin with metal ions (Reznichenko et al, 2006;Yu et al, 2005;Hayakawa et al, 2004;Chen et al, 2007). Catechin induces redox reactions or chelates with metal ions, especially transitional metal ions, which lead to bioactivity changes of catechin.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, it is important to know the interaction between EGCG and Zn 2+ and how their interaction modifies the risk of prostate cancer. Our previous studies revealed that biological activities of EGCG are altered in the presence of Zn 2+ , Cu 2+ , and Cd 2+ , and the results rely on (1) the relative concentrations of EGCG and metal ions, and (2) the order of their additions that might have led to the formation of complexes between EGCG and metal ions, which could lead to changes in the generation of free radicals within the cells (Yu et al, 2005;Chen et al, 2007). Nevertheless, there is little information available in literature about the interactions between EGCG and metal ions, especially with regard to their action on cell membrane of prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%